Application and Impact of Constructivism in Learning: A Tertiary Study - Wati, Darmanella Dian Eka; Dewi, Ratih Komala; Lasmana, Oria; Lufri, Lufri; Asrizal, Asrizal; Hardeli, Hardeli (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
The application of constructivist theories in literature reviews, particularly at the tertiary level, remains largely unexplored. This study aims to identify relevant literature reviews, what are their methodological features, and what are their objectives and subject matter regarding the application and impact of constructivism in learning. The method used in this tertiary study is systematic review. The purpose of the systematic review in this tertiary study research is to provide a careful summary of all available secondary research (literature review) in answering the research questions. In this study, researchers collected journal articles from Google Scholar, Eric, Science Direct, and Scopus online published in the period of 2014 to 2023. Based on the results of the collection and selection of articles by the inclusion and exclusion criteria, 15 articles were obtained. The article consists of 6 types of reviews, from 9 countries published in 15 Scopus and Sinta indexed journals. The results of this review show that the application of constructivism is carried out in learning activities in multi-disciplines. The impact of the application of constructivism is to improve learning outcomes, academic achievement, learning attitudes, and the effectiveness of learning activities.